Association between physical activity and diabetic complications among Bangladeshi type 2 diabetic patients. Issue 1 (January 2019) - Bukht, Mohammad Sadaat; Ahmed, Kazi Rumana; Hossain, Sahadat; Masud, Parisha; Sultana, Shuhana; Khanam, Rasheda
Abstract: Background: The aim of the study was to assess the association of physical activity (PA) with the presence of diabetes related complications among Bangladeshi type 2 diabetic subjects. Methods: This cross-sectional study was conducted in the Out Patient Department (OPD) of BIRDEM, Bangladesh. A group of 977 subjects were randomly selected and followed up. Diabetes was diagnosed following the WHO study group criteria. The level of PA was categorized into inactive/low (<150 min/week) and moderate-to-vigorous (≥150 min/week). The WHO recommended Asian criteria was used to identify general obesity. Retinopathy was detected by fundal photography, CKD by serum creatinine and hypertension was diagnosed clinically. Univariate and multivariate analyses were used to assess the associations of PA with diabetes related complications. Results: Out of the 977 subjects investigated, 468 were male and 509 were female (mean ± SD of age, 56 ± 8 years). In the study subjects, 74% were either inactive or in low PA and of them 65.1% were overweight/obese. Analysis showed that inactive/low PA was associated with all the three diabetes related complications (p < 0.001)–hypertension, retinopathy, and nephropathy. Multivariate analysis showed that inactive/low level of PA was strongly associated with complications like retinopathy (p < 0.001) and hypertension (p = 0.01) in the female patients. It was also found to be highly associated with retinopathy (p < 0.001) among the male patients. Conclusion: A large number of urban Bangladeshi population are involved only in low PA or remain inactive themselves, which is leading to obesity and it seems to have a strong association with diabetes related complications in this population.